N4-cytosine DNA methylation regulates transcription and pathogenesis in Helicobacter pylori. Issue 7 (22nd February 2018) - Kumar, Sumith; Karmakar, Bipul C; Nagarajan, Deepesh; Mukhopadhyay, Asish K; Morgan, Richard D; Rao, Desirazu N
Abstract: Many bacterial genomes exclusively display an N 4 -methyl cytosine base (m4C), whose physiological significance is not yet clear. Helicobacter pylori is a carcinogenic bacterium and the leading cause of gastric cancer in humans. Helicobacter pylori strain 26695 harbors a single m4C cytosine methyltransferase, M2.HpyAII which recognizes 5′ TCTTC 3′ sequence and methylates the first cytosine residue. To understand the role of m4C modification, M2.hpyAII deletion strain was constructed. Deletion strain displayed lower adherence to host AGS cells and reduced potential to induce inflammation and apoptosis. M2.hpyAII gene deletion strain exhibited reduced capacity for natural transformation, which was rescued in the complemented strain carrying an active copy of M2.hpyAII gene in the genome. Genome-wide gene expression and proteomic analysis were carried out to discern the possible reasons behind the altered phenotype of the M2.hpyAII gene deletion strain. Upon the loss of m4C modification a total of 102 genes belonging to virulence, ribosome assembly and cellular components were differentially expressed. The present study adds a functional role for the presence of m4C modification in H. pylori and provides the first evidence that m4C signal acts as a global epigenetic regulator in H. pylori .